Triple synergistic cancer targeting strategies utilizing redox-sensitive fattigated hyaluronic acid nanoparticles encapsulating doxorubicin - Ngo, Hai Van; Nguyen, Hy Dinh; Lee, Beom Jin (International Journal of Biological Macromolecules, 2025)
Antitumor potentials of dietary oleic acid (OA), primarily through enhancing intracellular lipid accumulation in various human cancers are hindered by poor selectivity and tumor targetability. Cancer cells are also challenged by high concentration of glutathione (GSH) and favorable binding affinity of hyaluronic acid (HA) to the CD44 (acidic cell surface adhesion protein) receptor. A novel conjugate (HA-CYS-OA, HOC) was synthesized by linking GSH-sensitive cystamine (CYS) to OA and HA. This amphiphilic HOC could self-assemble into redox-sensitive nanoparticles (HON) to co-deliver OA and encapsulated doxorubicin (DOX). HON synergistically enhanced anticancer efficacy by facilitating HA-mediated cellular uptake and GSH-triggered OA release in a targeted manner. Encapsulation of DOX in HON resulted in higher cellular uptake and more efficient DOX release compared to the commercially available liposomal DOX formulation. Furthermore, DOX-HON protected non-cancerous cells, while significantly increasing cytotoxicity and higher rate of apoptosis of human breast carcinoma cells, demonstrating superior selectivity indices. This enhanced performance was attributed to the triple synergistic actions of HA-mediated DOX targeting and OA-induced lipid accumulation from the redox-sensitive nanoformulation. Collectively, our results suggested that enzyme specific HON could be a bioactive and selective nanocarrier model for the co-delivery of fatty acids and chemotherapeutic drugs in synergistic cancer therapy.
Keywords: Anticancer activities; Cystamine; Doxorubicin; Fattigated nanoparticle; Lipid droplet overexpression; Lipid droplets; Overexpressions; Redox sensitives; Redox-responsive; Redox-responsive cystamine linker; Anticancer activity; Fattigated nanoparticles; Hyaluronic acid; Lipid droplet overexpression; Oleic acid; Redox-responsive cystamine linker